2019
DOI: 10.3899/jrheum.180958
|View full text |Cite
|
Sign up to set email alerts
|

Localized Myofascial Inflammation Revealed by Magnetic Resonance Imaging in Recent-onset Polymyalgia Rheumatica and Effect of Tocilizumab Therapy

Abstract: Objective.To assess the prevalence of myofascial inflammatory lesions visible by magnetic resonance imaging (MRI) and their changes after tocilizumab (TCZ) therapy in active polymyalgia rheumatica (PMR).Methods.We conducted a posthoc analysis of data from the TENOR study of TCZ monotherapy in PMR. The 18 patients each received TCZ injections at weeks 0, 4, and 8. The shoulder and pelvic girdles were assessed at baseline then at weeks 2 and 12 using T1- and T2- short-tau inversion recovery–weighted MRI. Radiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Various imaging modalities have been introduced in the diagnostic work-up of suspected PMR. Ultrasonography and magnetic resonance imaging (MRI) may reveal subacromialsubdeltoid bursitis, biceps tenosynovitis, glenohumeral synovitis, coxofemoral synovitis and/or trochanteric bursitis [2,[5][6][7][8][9]. These abnormalities are more accurately detected by MRI than ultrasonography [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various imaging modalities have been introduced in the diagnostic work-up of suspected PMR. Ultrasonography and magnetic resonance imaging (MRI) may reveal subacromialsubdeltoid bursitis, biceps tenosynovitis, glenohumeral synovitis, coxofemoral synovitis and/or trochanteric bursitis [2,[5][6][7][8][9]. These abnormalities are more accurately detected by MRI than ultrasonography [10].…”
Section: Introductionmentioning
confidence: 99%
“…MRI scans covering selected areas (e.g. shoulder and hip girdle) and also total body MRI may be helpful in the evaluation of PMR [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Typical findings in PMR include a characteristic pattern of symmetrical inflammation in the greater trochanter, acetabulum and ischial tuberosity, reported in 64% of patients with PMR in one study [64]. In another study by Laporte et al., all patients with new‐onset PMR had at least one site of myofascial inflammation, most commonly in the hips, followed by pubic symphysis, shoulders and ischial tuberosity [65]. Advantages of MRI over ultrasound include that MRI is more specific with less interobserver variation in the assessment of vasculitis.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…Another interesting and recent study by Laporte et al described localised, myofascial inflammations identified by MRI at the shoulder and pelvic girdles in patients with active, recent-onset PM. Myofascial findings might, therefore, aid in PM diagnosis (22). Involvement of muscles on MRI has not been found in RA (23) nor spondyloarthritis (24).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%